Operational design and modelling of fire event tracking system in wireless sensor networks - Omar Fouad, Mohammed; Burairah, Hussin; Abd Samad, Hasan Basari (Asian Research Publishing Network (ARPN), 2016)
In recent years, WSNs have been widely used for monitoring of environmental changes as they are capable of combining their sensing of a phenomenon with their computational functions and operate with limited resources to accomplish an intended task. Sensors can cooperatively monitor the surrounding environment and provide data that help in realizing the time evolution of the phenomenon and anticipating its effects. Consequently, such information would facilitate performing control actions that meet the predetermined goals. As distributed computing enables the exchange of real time data statistics obtained from various sources that need to be combined together to infer real abnormal conditions for management decisions. As tracking of an event depends on the event type, high-accuracy localization of an event such as fire is a serious challenge, where most of traditional detection systems depend on visualization (cameras) in making their control decision. Moreover, those systems concern the continuous detection of fire and do not provide reliable and feasible mechanism for tracking fire spread. This paper presents the design and modelling of a fire event tracking system that consists of indoor distributed sensor nodes and a powerful intelligent processing unit (controller) to detect fire events and compute information to provide desired safety decisions. Whenever the temperature in a premise increases, the system deploys cooperative centralized control functions to collect and process data statistics related to the fire. It exchanges direction, velocity, and/or position to take proper decision such as evacuating people from fire areas to a safe exit.